RNA Primer Extension Hinders DNA Synthesis by Escherichia coli Mutagenic DNA Polymerase IV - Tashjian, Tommy F.; Lin, Ida; Belt, Verena; Cafarelli, Tiziana M.; Godoy, Veronica G. (Frontiers in Microbiology, 2017)
In Escherichia coli the highly conserved DNA damage regulated dinB gene encodes DNA Polymerase IV, an error prone specialized DNA polymerase with a central role in stress-induced mutagenesis. Since DinB is the DNA polymerase with the highest intracellular concentrations upon induction of the SOS response, further regulation must exist to maintain genomic stability. Remarkably, we find that DinB DNA synthesis is inherently poor when using an RNA primer compared to a DNA primer, while high fidelity DNA polymerases are known to have no primer preference. Moreover, we show that the poor DNA synthesis from an RNA primer is conserved in DNA polymerase Kappa, the human DinB homologue. The activity of DinB is modulated by interactions with several other proteins, one of which is the equally evolutionarily conserved recombinase RecA. This interaction is known to positively affect DinB’s fidelity on damaged templates. We find that upon interaction with RecA, DinB shows a significant reduction in DNA synthesis when using an RNA primer. Furthermore, with DinB or DinB:RecA a robust pause, sequence and lesion independent, occurs only when RNA is used as a primer. The robust pause is likely to result in abortive DNA synthesis when RNA is the primer. These data suggest a novel mechanism to prevent DinB synthesis when it is not needed despite its high intracellular concentrations protecting thus genome stability.